Odpowiedzi

  • Użytkownik Zadane
2010-01-19T20:05:51+01:00
E)
/ 4x-2y=6
\ 3x-6y=12 /:3

4x - 2y = 6
x - 2y = 4

4x - 2y = 6
x = 4 + 2y

4(4 + 2y) - 2y = 6
x = 4 + 2y

16 + 8y - 2y = 6
x = 4 + 2y

6y = 6 - 16
x = 4 + 2y

6y = -10/:6
x = 4 + 2y

y = - 5/3
x = 4 + 2(-5/3)

y = -5/3
x = 4 - 3 1/3

y = -5/3
x = 2/3

f)
/3x-4y=14
\-2x+7y=-18/:(-2)

3x - 4y = 14
x - 3,5y = 9

3x - 4y = 14
x = 9 + 3,5y

3(9 + 3,5y) b- 4y = 14
x = 9 + 3,5y

27 + 10,5y - 4y = 15
x = 9 + 3,5y

6,5y = -13/: 6,5
x = 9 + 3,5y

y = - 2
x = 9 + 3,5*(-2)

y = -2
y = 9 - 7

y = - 2
x = 2



3/82
e)
/ 2x+y=14 /:2
\ 5x+4y=17

x + 0,5y = 7
5x + 4y = 17

x = 7 - 0,5y
5 * (7 - 0,5y) + 4v = 17

x = 7 - 0,5y
35 - 2,5y + y = 17

x = 7 - 0,5y
-1,5y = 17 - 35

x = 7 - 0,5y
- 1,5y = - 18 /: (-1,5

x = 7 - 0,5y
y = 12

x = 7 - 0,5*12
y = 12

x = 7 - 6
y = 15

x = 1
y = 15



1 1 1
2010-01-19T20:10:48+01:00

e)
4x-2y=6|:2
3x-6y=12

2x-y=3
3x-6y=12

-y=3-2x|:(-1)
3x-6y=12

y=-3+2x
3x-6(-3+2x)=12
3x+18-12x=12
-9x=9
x=-1

y=-3+2(-1)
y=-3-2
y=-5


f)
x-4y=14
-2x+7y=-18

x=14+4y
-2(14+4y)+7y=-18
-28-8y+7y=-18
-y=10
y=-1

x=14+4(-1)
x=14-4
x=10



3/82
e)
2x+y=14
5x+4y=17

y=14-2x
5x+4(14-2x)=17
5x+56-8x=17
-3x=-39
x=13

y=14-2*13
y=14-26
y=-12